Identifikasi Karakteristik Genetik Sapi Peranakan Ongole di Peternakan Rakyat (The Identification of Genetic Characteristic of Ongole Grade Cattle in Smallholder Farmers) - Hartati (Hartati); Sumadi (Sumadi); Tety Hartatik (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
The aim of this research was to identity genetic characteristic of Ongole Grade cattle and to analyse the diversity of Ongole grade cattle in smallholder farmers. This research was conducted at breeding stock in East Java and Central Javainclude Tuban, Lamongan and Blora regencies, since June until December 2008. The animal use were PO cattle of 18 months until 24 months of age and cow of 24 months until 36 months of age or have once of calving as many 30 headfrom location, were used as sampling for the observation of genetic diversity which was based on quantitative and qualitative characteristic. Whole blood collection was conducted to get the data of polymorphism DNA microsatelliteby using technology of PCR and elektroforesis. Data and information were analysed in descriptive, explanatory and laboratoris. The result showed that Blora subpopulation had genetic distance which was close to Tuban subpopulationcompared to Lamongan. The result of molecular genetic analyses by using microsatellite showed that highest frequency alel was presented by HEL9 locus at Tuban population. Heterozigosity value at 3 subpopulation of PO cattle was verylow, representing an indication of leading to inbreeding cases.(Key words : Genetic characteristic, PO cattle, Smallholder farmers)